Optimization of Coffee Bean Extraction Using Subcritical Water: A Response Surface Methodology Approach for Maximizing Caffeine and Antioxidant Yield - Sutrisno, Sutrisno; Yulianto, Mohamad Endy; Ariwibowo, Didik; Paramita, Vita; Utari, Febiani Dwi; Azhara, Belinda; Monawisya, Abitha; Rizki, Muhammad (Indonesian Food Science and Technology Journal, 2025)
This study explores the optimization of Subcritical Water Extraction (SWE) for maximizing caffeine and antioxidant yields from coffee beans using Response Surface Methodology (RSM). A Central Composite Design (CCD) was employed to evaluate the interaction effects of three key variables: temperature, solvent volume, and extraction time. As an eco-friendly alternative to conventional extraction methods, SWE was optimized based on these parameters. Statistical analysis confirmed their significant influence on bioactive compound recovery, with optimal conditions—162.440 °C, 28.409 mL of solvent, and 27.389 minutes—yielding 0.395 mg/mL caffeine and 27.039 μg/mL antioxidants, achieving a composite desirability value of 0.873. SEM analysis revealed significant structural degradation in the SWE-treated coffee extract, enhancing the release of caffeine and antioxidants by increasing porosity and cell wall disruption. This improved extraction efficiency, combined with SWE’s solvent-free nature and scalability, reinforces its role as an efficient method for extracting bioactive compounds from coffee, supporting its adoption as a green technology in sustainable food processing.